Designing Majuah-juah Tongging Hotel Resort with Neo- Vernacular Architecture Approach - Ilham Azhar Badrawi; Wahyu Utami (International Journal of Architecture and Urbanism, 2019)
Tongging Village is a tourist village located on the shores of Lake Toba. The natural wealth is owned by Tongging villages such as Sipiso-Piso waterfall which is the highest waterfall in Indonesia, also Sapo Juma which is a flower garden and camping area not far from the site location. However, with the natural wealth of various tourist areas in Tongging Village has not been developed optimally. Accommodation in the village is also still very restricted because of this the need for supporting facilities that add visitors to the region. The application of Neo-Vernacular architecture aims to revive the traditional Siwaluh Jabu house which many people have forgotten. In this building, the concept of neo-vernacular architecture is seen regarding physical and non-physical aspects. If viewed from a physical point of view, this building uses materials and ornaments in traditional Karo houses and is also seen on the non-physical side of a traditional Karo house use double-loaded corridors and more flexible use of space. A resort Hotel in Tongging village that applies Neo-Vernacular architecture is expected to be an indicator of increased tourism and a reminder of traditional homes in the villages of Tongging and also North Sumatra.